Perhitungan Break Even Point (BEP) dan Margin of Safety (MOS) Sebagai Alat Perencanaan Laba - Thania Putri Liestiana; Ira Novianty (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This research was conducted on UMKM Makroni NR Ciamis who have not done a good profit planning. The purpose of this study was to find out how profit planning was carried out, the number of Break Even Points (BEP) and Margin of Safety (MOS) at UMKM Makroni NR Ciamis. The research method applied is descriptive method with a quantitative approach. The types of data used are qualitative data and quantitative data with the data sources being primary data and secondary data. Data collection techniques used are interviews and documentation. The steps taken are to classify costs into fixed costs and variable costs, calculate contribution margin, BEP, target sales volume and MOS. Based on the calculation, the BEP generated is Rp. 5,466,406 and the resulting MOS is 94.33%. The results of this study are expected to help companies in carrying out optimal profit planning through the calculation of BEP and MOS.